APPLICATION OF ADVENTURE QUEST TO UNDERSTANDING SUBJECT-PREDICATE-OBJECT-DESCRIPTION (S-P-O-K) STRUCTURE IN INDONESIAN LEARNING FOR GRADE 3 ELEMENTARY SCHOOL STUDENTS - Wahyuningsih, Ika; Nugraheni, Aninditya Sri (Jurnal Ilmiah Didaktika, 2025)
Many lower-grade students, particularly in grade 3 of SD/MI, face difficulties in understanding and applying the Subject, Predicate, Object, and Adverbial (S-P-O-K) structure accurately. This study explores the use of the Adventure Quest strategy, adapted from online role-playing games, as an innovative learning model to enhance students’ comprehension of SPOK through engaging, story-based missions. Using a descriptive qualitative design, the research analyzes classroom interactions and students’ responses during implementation. The findings reveal that the Adventure Quest approach increases students’ motivation, participation, and confidence in constructing structured sentences. Students reported high satisfaction and improved understanding of SPOK concepts. This study contributes a novel pedagogical adaptation by integrating game-based adventure elements into Indonesian language learning, demonstrating its potential to create an active and contextual learning environment.